Gypenoside LVI attenuates foam cell formation by promoting cholesterol export and inhibiting inflammation response - Chun-Yan Shen (Journal of Functional Foods, 2018)
Gynostemma pentaphyllum was widely consumed in China because of its various pharmacological activities. Numerous studies have confirmed the beneficial effects of G. pentaphyllum. However, the ultimate compounds responsible for its inhibitory effects on foam cell formation were still unknown. Gypenoside LVI (GPLVI), a dammarane-type gynosaponin was isolated and identified from G. pentaphyllum. Treatment of GPLVI successfully attenuated foam cell formation, as evidenced by Oil Red O staining, TG and cholesterol contents, and Dil-ox-LDL uptake analyses. GPLVI displayed significant inhibitory effects on secretion of IL-6 and IL-1β. In contrast, production of TNF-α was not markedly reduced. GPLVI also markedly induced ABCG1, SRB1 and LXRα expression. Additionally, GPLVI significantly blocked phosphorylation of ERK and JNK. Taken together, our results suggested that GPLVI might be responsible for the inhibitory effect of G. pentaphyllum on ox-LDL-induced foam cell formation mainly by promoting cholesterol efflux and inhibiting inflammatory response.